In the deep sea of Hyponatremia: A case series (Bangladesh Journal of Medicine, 2024)
Hyponatremia is a matter of concern in clinical practice. Hyponatremia can be associated both low or high tonicity and even with normal tonicity. Although severity and morbidity varies widely but sometimes serious hazard can occur from misdiagnosis or late diagnosis. In these 3 case we will discuss different pattern of presentations of hyponatremia. Megestrol acetate is a synthetic progestin used to treat the symptoms of loss of appetite and wasting syndrome in people with AIDS-related cachexia, breast cancer or endometrial cancer. Herein, we report a case of 32 years’ female presented with clinical and biochemical features of central adrenal insufficiency who was taking megestrol acetate chronically. Pituitary function was otherwise essentially normal. Another case about a 46 year old male who was getting treatment for schizophrenia and later found to have hypopituitarism. Our last case about a male of 35 years old who was also diagnosed to have pituitary insufficiency.Bangladesh J Medicine 2024; 35(1): 33-37